Halal Awareness Behavior of Producers and Consumers from Maqashid Sharia Perspective - Syauqillah, Muhammad; Rofiq, Aunur; Khusnudin, Khusnudin; Asnawi, Nur (Tasharruf: Journal Economics and Business of Islam, 2024)
The growth of the global Muslim population, especially in Indonesia, which has the largest Muslim population, must be balanced with the Muslim community's awareness of halal products. This research aims to analyze the influence of Islamic principles on the awareness of producers and consumers in the production and consumption of Halalan Thayyiban products in Indonesia after the implementation of Law Number 33 of 2014 concerning Halal Product Guarantees. Using qualitative methods with a psychological approach, data was collected from documentary sources such as the Internet, journals, books, laws, and articles. The research findings demonstrated that Islamic principles significantly influenced consumer and producer awareness and behavior within the context of halal products. Specifically, the safeguarding of religion, life, lineage, property, and intellect had notably heightened manufacturers' adherence to halal standards while simultaneously enhancing consumer consciousness regarding the importance of products that are safe, hygienic, and of superior quality. These conclusions emphasized that the integration of Islamic principles not only facilitated compliance with Sharia law but also elevated the quality and safety experienced by consumers, ultimately aligning with the attainment of the Halalan Thayyiban concept.